A Comparison of Nonstaggered Compact FDTD Schemes for the 3D Wave Equation - Kowalczyk, Konrad; van Walstijn, M. (Proc. IEEE Int. Conf. on Acoustics, Speech, and Signal Processing (ICASSP), 2010)
This paper aims at providing a better insight into the 3D approximations of the wave equation using compact finite-difference time-domain (FDTD) schemes in the context of room acoustic simulations. A general family of 3D compact explicit and implicit schemes based on a nonstaggered rectilinear grid is analyzed in terms of stability, numerical error, and accuracy. Various special cases are compared and the most accurate explicit and implicit schemes are identified. Further considerations presented in the paper include the direct relationship with other numerical approaches found in the literature on room acoustic modeling such as the 3D digital waveguide mesh and Yee's staggered grid techniqu
LMS::939
Keywords: Acoustic propagation; acoustic signal processing; architectural acoustics; finite-difference time-domain (FDTD) methods